DOI: 10.18174/528572
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term effects of early nutrition in broiler chickens

Abstract: Chapter 1 General introduction Chapter 2 Effects of early nutrition and transport of 1-day-old chickens on production performance and fear response Chapter 3 Intestinal epithelium integrity after delayed onset of nutrition in broiler chickens Chapter 4 Early and later life effects of early nutrition and sanitary conditions on humoral immunity in broiler chickens Chapter 5 Effects of early nutrition and sanitary conditions on oral tolerance and antibody responses in broiler chickens Chapter 6 General discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 183 publications
(512 reference statements)
2
3
0
Order By: Relevance
“…These results underline the importance of the provision of feed to broiler chicks immediately at the hatchery as the delay in feeding time can have negative consequences on the performance of these chickens in the early stages of production. In line with previous studies ( de Jong et al, 2017 ; Hollemans, 2020 ), BW of early-fed chickens in the current study was always higher than the BW of non-early-fed chickens until day 37 of age. In general, the variation in the BW between early-fed and delayed-fed chicks depends on the experimental context and feed deprivation times, and the results of the current study seemed to confirm that early feeding has long-term effects on the absolute values of BW ( Hollemans, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results underline the importance of the provision of feed to broiler chicks immediately at the hatchery as the delay in feeding time can have negative consequences on the performance of these chickens in the early stages of production. In line with previous studies ( de Jong et al, 2017 ; Hollemans, 2020 ), BW of early-fed chickens in the current study was always higher than the BW of non-early-fed chickens until day 37 of age. In general, the variation in the BW between early-fed and delayed-fed chicks depends on the experimental context and feed deprivation times, and the results of the current study seemed to confirm that early feeding has long-term effects on the absolute values of BW ( Hollemans, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies ( de Jong et al, 2017 ; Hollemans, 2020 ), BW of early-fed chickens in the current study was always higher than the BW of non-early-fed chickens until day 37 of age. In general, the variation in the BW between early-fed and delayed-fed chicks depends on the experimental context and feed deprivation times, and the results of the current study seemed to confirm that early feeding has long-term effects on the absolute values of BW ( Hollemans, 2020 ). However, the current study also showed that early feeding resulted in worse cleanliness and gait scores at the slaughter age compared to delayed nutrition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lower body weight in HH as compared to OH chickens is likely caused by the delay in access to feed and water ( 82 ). Although studies showed that the duration of the effect of the first feeding moment on body weight may vary, due to variation in post-hatch feed deprivation time and the ability of delayed-fed chickens to show compensatory growth ( 82 , 83 ), on-farm hatched chickens usually show a higher body weight at least during the first weeks of life ( 38 41 ). It is unclear why we observed such short-term effects of hatching conditions on body weight development in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why differences in broiler resilience were more evident in the response to colibacillosis, which was induced at day 8 of age, compared to necrotic enteritis that was induced at day 21 of age. Hollemans (2020) concluded in his thesis that early feeding may improve resistance to infectious diseases during the first week of age because higher IgM natural antibodies were found in early compared to delay fed broilers up to 7 days of age, whereas at older ages no difference in systemic humoral immunity was found.…”
Section: Maturation Of the Immune Systemmentioning
confidence: 99%